Experimental research of noises integral converters of tension in chains of galvanic isolation - Кардашук, Володимир Сергійович (Eastern-European Journal of Enterprise Technologies, 2012)
Galvanic isolation in circuits of the signals transmission and reception is widely used in the communication interface block RS-485. Integrated voltage transducer noises, used in such circuits, are the source of interference and they affect the quality of information transmission via the interface RS-485. The article examines and suggests the methods of reducing the influence of common-mode interferences for integrated voltage transducers produced by Traco Power AG, for their application in galvanic isolation chains RS-485. The research results show that the common-mode interferences generate themselves in the output circuit of integrated voltage transducer, as a result of switching current step of the output transistors. The current step is the result of different opening and closing moment of the output transistors, which leads to the transition process with large amplitude and duration. On the basis of experimental studies the application of Epcos inductive filters along with integrated voltage transducer, which reject interferences, reduces considerably the effect of integrated voltage transducer noises on the quality of signals transmission galvanic isolation circuits and increases the noise immunity of communication interface blocks RS-485